Greiser et al. (2023) Higher soil moisture increases microclimate temperature buffering in temperate broadleaf forests - Data and Code - Greiser, Caroline; Kopecký, Martin; Macek, Martin; Hederová, Lucia; Vico, Giulia; Wild, Jan (Stockholm University, 2023)
Abstract of the article to which the data and code belong:

Forest canopies can buffer the understory against temperature extremes often creating cooler microclimates during warm summer days compared to temperatures outside the forest. The buffering of maximum temperatures in the understory results from a combination of canopy shading and air cooling through soil water evaporation and plant transpiration. Therefore, buffering capacity of forests depends on canopy cover and soil moisture content, which are increasingly affected by more frequent and severe canopy disturbances and soil droughts. The extent to which this buffering will be maintained in future conditions is unclear due to the lack of understanding about the relationship between soil moisture and air temperature buffering in interaction with canopy cover and topographic settings. We explored how soil moisture variability affects temperature offsets between outside and inside the forest on a daily basis, using temperature and soil moisture data from 54 sites in temperate broadleaf forests in Central Europe over four climatically different summer seasons. Daily maximum temperatures in forest understories were on average 2 °C cooler than outside temperatures. () The buffering of understory temperatures was more effective when soil moisture was higher, and the offsets were more sensitive to soil moisture on sites with drier soils and on sun-exposed slopes with high topographic heat load. Based on these results, the soil-water limitation to forest temperature buffering will become more prevalent under future warmer conditions and will likely lead to changes in understory communities. Thus, our results highlight the urgent need to include soil moisture in models and predictions of forest microclimate, understory biodiversity and tree regeneration, to provide a more precise estimate of the effects of climate change.

List of files:

02_model_offset_from_soilmoist_rev.r => R-script for the statistical analysis

model_data_complete_figshare.csv => cleaned and complete data for the statistical analysis

model_data_4thday_figshare.csv => cleaned and "thinned" data for the statistical analysis

README.txt => metadata describing columns in the dataframes and the environment of the R-script
Keywords: Forestry sciences not elsewhere classified; Climate change processes; Soil physics; Climate Science; Klimatvetenskap; Forest Science; Skogsvetenskap